INTERPRETATION OF SIGNIFICANCE OF GENDER EQUALITY IN THE WORLD COMMUNITY - Malika Uraimjonova Kahramon kizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article describes the relevance of the issue of gender equality, which is considered an urgent issue all over the world. The article also describes the concept of "gender equality", which is widely used in the international community - men and women can participate in the political, social and economic spheres of the state and society on an equal basis.